Correlation Of Intracerebral Hemorrhage Score And 30-Day Mortality In Hemorrhagic Stroke - Alauddin, Md; Hossain, Md. Ismail; Moinuddin, Syed M.; Alam, Md. Saiful; Sanaullah, Mohammad; Quader, Mahfuzul; Faruk, Omar; Karim, Md. Rabiul; Reza, Abul Hasan Md Touhidur (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Hemorrhagic Stroke (HS) is a devastating subtype of stroke with high mortality. The Intracerebral Hemorrhage Score (ICH Score) is a globally accepted prognostic tool for predicting 30-day mortality. To determine correlation between ICH Score and 30-day mortality in patients with HS at Neurosurgery Department of a tertiary hospital in Bangladesh. Materials and methods: A prospective observational study was conducted over 18 months, enrolling 288 adults with HS. The ICH Score was calculated at the time of admission. Patients were followed-up at 30-day by Glasgow Outcome Scale (GOS). Spearman’s correlation analysis was performed to determine correlation between ICH score and 30-day mortality. Results: The patients mean age was 59.6 years and 27 (9.5%) underwent surgical intervention. 30-day mortality rate was 42.25%. Strong positive correlation of ICH score was found with 30-day mortality (rho=0.984) and negative correlation was found with GOS score at 30-day (rho= 0.583). Mortality escalated with higher scores: 2.9% (Score 0), 27.1% (Score 1), 33.7% (Score 2), 72.9% (Score 3), 89.5% (Score 4) and 100% (Scores 5). Conclusions: The ICH score had positive correlation with 30-day mortality and acceptable in predicting 30-day mortality in HS. JCMCTA 2025 ; 36 (2) : 19-24